2008
DOI: 10.1038/ncb1727
|View full text |Cite
|
Sign up to set email alerts
|

The HECT-domain ubiquitin ligase Huwe1 controls neural differentiation and proliferation by destabilizing the N-Myc oncoprotein

Abstract: Development of the nervous system requires that timely withdrawal from the cell cycle be coupled with initiation of differentiation. Ubiquitin-mediated degradation of the N-Myc oncoprotein in neural stem/progenitor cells is thought to trigger the arrest of proliferation and begin differentiation. Here we report that the HECT-domain ubiquitin ligase Huwe1 ubiquitinates the N-Myc oncoprotein through Lys 48-mediated linkages and targets it for destruction by the proteasome. This process is physiologically impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
275
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(285 citation statements)
references
References 44 publications
(5 reference statements)
7
275
0
1
Order By: Relevance
“…Mule belongs to the HECT-domain-containing E3 ligase family, which is known to catalyze only one type of polyubiquitination linkages (43), K48-linked polyubiquitination of substrates including p53, Mcl-1, N-Myc, and Cdc6 (33,(35)(36)(37). To determine whether Mule catalyzes K48-linked polyubiquitination of Miz1, we performed the in vitro ubiquitination assay in the presence of Ub (K48O), in which all lysines in ubiquitin were mutated to arginines except K48, or Ub (K63O).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mule belongs to the HECT-domain-containing E3 ligase family, which is known to catalyze only one type of polyubiquitination linkages (43), K48-linked polyubiquitination of substrates including p53, Mcl-1, N-Myc, and Cdc6 (33,(35)(36)(37). To determine whether Mule catalyzes K48-linked polyubiquitination of Miz1, we performed the in vitro ubiquitination assay in the presence of Ub (K48O), in which all lysines in ubiquitin were mutated to arginines except K48, or Ub (K63O).…”
Section: Resultsmentioning
confidence: 99%
“…The HECT domain-containing ubiquitin ligase (E3) Mule (also known as Ureb1, LASU1, HUWE1, ARF-BP1, or HectH9) plays a critical role in proteasomal degradation of several proteins (33)(34)(35)(36)(37), and is involved in regulation of apoptosis (33). Mule has two Armadillo (ARM) repeat-like domains (ARLD1 spanning amino acids 104-374, and ARLD2 spanning amino acids 424-815), a ubiquitin-associated (UBA) domain (amino acids 1317-1355), a WWE (amino acids 1617-1678), and a well-conserved BH3 domain (amino acids 1972-1994) at its N terminus, and a HECT domain (amino acids 4016-4374) is at its C terminus (33,(38)(39)(40).…”
mentioning
confidence: 99%
“…32,33 Recently, the HectH9/Huwe1 ubiquitin-protein ligase has been shown to degrade N-Myc protein during neuronal differentiation. 34 In the current study, we have identified the ubiquitin-protein ligase NEDD4, which is a member of the HECT ubiquitin-protein ligase family, 25,26 as a novel regulator of Myc protein ubiquitination and degradation. Our data demonstrate that NEDD4 directly binds to N-Myc protein, and targets N-Myc protein for ubiquitination by the ubiquitin conjugating enzymes (E2) UbcH5a and UbcH5b.…”
Section: Discussionmentioning
confidence: 99%
“…Mule was first identified as a ubiquitin ligase for an anti-apoptotic Bcl-2 family protein, Mcl-1 (Zhong et al 2005). Mule is also known as ARF-BP1, Ureb1, LASU1, HUWE1, or HectH9, and promotes ubiquitin-proteasomal degradation of multiple substrates, including p53, c-Myc, Cdc6, histones, N-Myc, Miz1, TopBP1, and Polb (Adhikary et al 2005;Chen et al 2005;Zhong et al 2005;Hall et al 2007;Liu et al 2007;Herold et al 2008;Zhao et al 2008;Parsons et al 2009;Yang et al 2010). However, whether any of these existing or unidentified substrates mediate the major function of Mule in the DNA damage response remains elusive.…”
mentioning
confidence: 99%